Ubharatā grāmīṇa netrtva - Rāṭhaura, Jagadīśa Siṃha (Prakāśa Buka Ḍipo, 1982)
On the emerging patterns of rural political leadership in India; study based on a survey of the Rohilkhand region of Uttar Pradesh.